Program Literasi Interaktif “CERDAS BACA – CERDAS BERANI” - Sardi Pranata; Adam Tbn; Angel Kristina Panggabean; Ayu Mora Simarmata; Diniwaty Marbun; Estefanie Lamtiur Gultom; Fanny Putri; Grace Zipora Sembiring; Marcella Febrina Br Tarigan; Mutiara Seven Manalu; Nazwa Alya Fasya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This mini research was conducted at Anugerah Kasih Orphanage to identify developmental issues among children, particularly related to their self-confidence and reading ability. Observations and interviews showed that several children demonstrated low confidence in communication and had not yet achieved fluent reading skills at the elementary school level. This study employed a qualitative method through observation, interviews, and the use of educational interventions, including educational videos, interactive quizzes, and pop-up books. The results indicate that these learning media effectively increased the children's learning motivation, improved their self-confidence, and enhanced their reading skills. Therefore, the use of varied educational media is recommended to support children's development in orphanage settings.